1991
DOI: 10.1002/ijc.2910470222
|View full text |Cite
|
Sign up to set email alerts
|

Oncofetal mucin Ml epitope family: Characterization and expression during colonic carcinogenesis

Abstract: The gastric mucin M1 antigens, markers associated with colonic carcinogenesis, have been characterized by new antimucin monoclonal antibodies (MAbs). These MAbs, obtained against mucins isolated from a human ovarian mucinous cyst (MAbs 19M1, 21M1 and 45M1) and from a pancreatic adenocarcinoma (MAb 96RA), were compared with 5 other anti-M1 mucin MAbs described previously, which characterized the a, b, c, d and e mucin M1 epitopes. Using immunoperoxidase, these new MAbs exclusively stained the surface gastric ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 24 publications
3
114
0
Order By: Relevance
“…[15][16][17][18] HGM is a specific marker for core protein of gastric foveolar cells. 19,20) The correlations between positivity to these antibodies and clinicopathologic features suggested that cell differentiation is inversely associated with tumor growth and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] HGM is a specific marker for core protein of gastric foveolar cells. 19,20) The correlations between positivity to these antibodies and clinicopathologic features suggested that cell differentiation is inversely associated with tumor growth and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We selected three immunohistochemical markers for cell differentiation: MUC2 for intestinal goblet cells, [12][13][14] CD10 for small intestinal brush border [15][16][17][18] and human gastric mucin (HGM) for gastric differentiation. 19,20) A representative section from each tumor was processed for immunohistochemical staining with monoclonal antibodies against MUC2 (Novocastra, Newcastle-upon-Tyne, UK, diluted 1:200), CD10 (Novocastra, diluted 1:200) and HGM (45M1, Novocastra, diluted 1:50). Four-micron-thick sections were cut, deparaffinized in xylene and dehydrated in an ethanol series.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in SHGFP-MUC5AC/CK mobility between the granule and endoplasmic reticulum were assessed by determining the apparent or effective diffusion coefficients (D eff ) (40), defined as the mean squared displacement of SHGFP-MUC5AC/CK over time. D eff integrates the absolute diffusion coefficient, which is largely due to the viscosity of the compartment, and effects caused by interactions and collisions with other proteins components.…”
Section: Figmentioning
confidence: 99%
“…18 -20 On the other hand, de novo appearance of a secreted mucin normally found in the stomach, MUC5AC, has been described in colon carcinomas. [21][22][23] Thus, mucinous differentiated cells are present in colorectal carcinomas and more particularly in mucinous carcinomas and in signet ring cell carcinomas. Until now, the significance of a differentiation characteristic into a mucin-secreting phenotype with regard to the tumor development is still unknown.…”
Section: Abstract: Colon Carcinoma Cells; E-cadherin; Mucins; Heparamentioning
confidence: 99%